Características demográficas, genéticas, fenotípicas, otoras, funcionais, respiratórias, de qualidade de vida e respostas à terapia de reposição enzimática dos pacientes com diagnóstico de doença de pompe de início tardio no Estado do Ceará - Nogueira, Andrea da Nobrega Cirino (2017)
Late-Onset Pompe Disease (DPIT) is the juvenile-adult variant of an autosomal recessive disease caused by a deficiency of the α-glycosidase (GAA) enzyme, which is characterized by the accumulation of glycogen in the body's muscle cells. There is a wide variation in its clinical spectrum, from the age of onset of symptoms to the rate of disease progression and different phenotypes. Respiratory symptom may be the first manifestation of the disease and presents a high incidence, being the main cause of death. In this context, diaphragmatic involvement is the most important aspect. The realization of studies to evaluate the general phenotypic aspects and their interrelationships with the diaphragmatic force in individuals with LOPD is still incipient in the world, especially in Brazil. OBJECTIVES: to describe the demographic, genetic, phenotypic, functional and quality of life characteristics of patients diagnosed with LOPD of the State of Ceará; To establish correlations between these variables with the patients' diaphragmatic strength; To describe the evolution of clinical, functional and QOL parameters, and in particular, the response to ERT during 20 to 25 months of outpatient follow-up. METHOD: This was a prospective, descriptive and observational cohort study in humans. The study was carried out in the Respiration and Gastroenterology Laboratories of the Faculty of Medicine and the Walter Cantídio University Hospital of the Federal University of Ceará, from April 2015 to May 2017. The population was composed of five patients with confirmed molecular diagnosis of LOPD with indication of ERT in the State of Ceará. Adult patients, older than 18 years of age, of both genders were included. Dosages of muscle and biochemical lesion markers were performed in the blood; Evaluation and quantification of fatty infiltration of the skeletal muscle through nuclear magnetic resonance (MRI) examination; Assessment of respiratory function (spirometry) and maximal respiratory pressures, in the sitting and lying positions; chest X-ray; Evaluation of the thickness and strength of the diaphragm, through examination of MRI and high resolution chest computed tomography (HRCT), peripheral muscle strength of palmar, sleep, quality of life (QoL), International Classification of Functionality (IFC) and functional evolution (six-minute walk test - 6MWT); With outpatient follow-up and monitoring of patients' ERT. The diaphragmatic force was measured by the determination of transdiaphragmatic pressure (Pdi), using the high resolution esophageal manometry technique (MEAR) in calm breathing and during voluntary hyperventilation maneuver. The study approved by the Research Ethics Committee according to resolution 466/2012 of the National Health Council under opinion nº 1.867.794. RESULTS: the mean age at onset of symptoms was 30 years, ranging from 26 to 45 years. The type of initial symptom 13 was motor, followed by respiratory, the latter being the most relevant manifestation in 2 of the 5 patients, including the need for non-invasive nocturnal ventilatory support. In laboratory tests, hepatic enzymes, creatine phosphokinase increase and hypercholesterolemia were observed in most cases. The most frequent clinical manifestations were fatigue, difficulty in walking, intolerance to exercise and dyspnea. Two of the five patients presented with paradoxical respiratory movement. Musculoskeletal manifestations included postural changes, scoliosis, kyphosis and lordosis, and the difficulty of performing activities against gravity, from getting up from lying down and sitting down, crouching and picking up objects on the floor. In the MRI imaging studies, atrophy of the paravertebral, thigh and tongue musculature associated with the degen Grease. All patients had respiratory system impairment, with FVC <80% reduction predicted. An important reduction in diaphragmatic thickness was observed in the imaging examinations in all patients. The Pdi was reduced and correlated inversely with the variation of FVC and FEV1 in seated position, PEF, BMI, diaphragm thickness, PEmax, the difference of sitting PEmax and QV Physical and mental health, functional capacity, pain and mental health). The IFC showed functionality compromised in the aspects Body function, Activity and Participation. Patients presented different levels of disability that compromised work, productivity, social and family roles. During the 20-month outpatient follow-up, there was a significant reduction in the distance walked on the 6MWT, but at the same time, an increase in the social and mental health scores of the QOL questionnaire. CONCLUSIONS: In general, the described characteristics of the patients did not differ from those published in the literature up to the present date. There was an inverse correlation between Pdi measurement and pulmonary function, diaphragm thickness and QV. There was a significant reduction in the distance covered in the 6MWT and improvement in the scores of mental health components and social aspects of the QOL questionnaire. Due to the diversity of human activity problems deriving from the DPIT, it is necessary that the interventions in the field of functional recovery have a multidisciplinary approach, in order to guarantee their effectiveness.